Endovascular ultrasound renal denervation to treat hypertension (RADIANCE-HTN SOLO): a multicentre, international, single-blind, randomised, sham-controlled trial. Issue 10137 (9th June 2018) - Azizi, Michel; Schmieder, Roland E; Mahfoud, Felix; Weber, Michael A; Daemen, Joost; Davies, Justin; Basile, Jan; Kirtane, Ajay J; Wang, Yale; Lobo, Melvin D; Saxena, Manish; Feyz, Lida; et al.
Summary: Background: Early studies suggest that radiofrequency-based renal denervation reduces blood pressure in patients with moderate hypertension. We investigated whether an alternative technology using endovascular ultrasound renal denervation reduces ambulatory blood pressure in patients with hypertension in the absence of antihypertensive medications. Methods: RADIANCE-HTN SOLO was a multicentre, international, single-blind, randomised, sham-controlled trial done at 21 centres in the USA and 18 in Europe. Patients with combined systolic–diastolic hypertension aged 18–75 years were eligible if they had ambulatory blood pressure greater than or equal to 135/85 mm Hg and less than 170/105 mm Hg after a 4-week discontinuation of up to two antihypertensive medications and had suitable renal artery anatomy. Patients were randomised (1:1) to undergo renal denervation with the Paradise system (ReCor Medical, Palo Alto, CA, USA) or a sham procedure consisting of renal angiography only. The randomisation sequence was computer generated and stratified by centres with randomised blocks of four or six and permutation of treatments within each block. Patients and outcome assessors were blinded to randomisation. The primary effectiveness endpoint was the change in daytime ambulatory systolic blood pressure at 2 months in the intention-to-treat population. Patients were to remain off antihypertensive medications throughout the 2 months of follow-up unless specified blood pressure criteria were exceeded. Major adverse events included all-cause mortality, renal failure, an embolic event with end-organ damage, renal artery or other major vascular complications requiring intervention, or admission to hospital for hypertensive crisis within 30 days and new renal artery stenosis within 6 months. This study is registered withClinicalTrials.gov, numberNCT02649426 . Findings: Between March 28, 2016, and Dec 28, 2017, 803 patients were screened for eligibility and 146 were randomised to undergo renal denervation (n=74) or a sham procedure (n=72). The reduction in daytime ambulatory systolic blood pressure was greater with renal denervation (−8·5 mm Hg, SD 9·3) than with the sham procedure (−2·2 mm Hg, SD 10·0; baseline-adjusted difference between groups: −6·3 mm Hg, 95% CI −9·4 to −3·1, p=0·0001). No major adverse events were reported in either group. Interpretation: Compared with a sham procedure, endovascular ultrasound renal denervation reduced ambulatory blood pressure at 2 months in patients with combined systolic–diastolic hypertension in the absence of medications. Funding: ReCor Medical.